2001
DOI: 10.1016/s0176-2680(01)00046-5
|View full text |Cite
|
Sign up to set email alerts
|

Intervention in risky export markets: insurance, strategic action or aid?

Abstract: Because the use of trade policy is limited by international institutional arrangements, governments pursuing a policy of export promotion may want to use more indirect instruments to achieve their objectives. In that context, this paper focuses on the public provision of export insurance. While the prime objective is insurance against the risk of default faced by firms exporting to risky markets, these insurance programmes are often embedded in more global policy objectives of the exporting country's governmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 19 publications
0
32
0
1
Order By: Relevance
“…Wang and Barrett (2002) gave a new empirical look at the longstanding question of the effect of exchange rate volatility on international trade flows by investigating the case of Taiwan's exports to the United States. Dewit (2001) performed a survey on the public provision of export insurance where the objective was insurance against the risk of default faced by firms exporting to risky markets, these insurance programs were often embedded in more global policy aims of the exporting country's government. The study tried to understand how premium rating of official export insurance was changed by strategic export promotion and the pursuit of other political objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Barrett (2002) gave a new empirical look at the longstanding question of the effect of exchange rate volatility on international trade flows by investigating the case of Taiwan's exports to the United States. Dewit (2001) performed a survey on the public provision of export insurance where the objective was insurance against the risk of default faced by firms exporting to risky markets, these insurance programs were often embedded in more global policy aims of the exporting country's government. The study tried to understand how premium rating of official export insurance was changed by strategic export promotion and the pursuit of other political objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Základní publikací, věnující se popisu a ekonomické analýze exportních úvěrových institucí, je Stephens (1999), který podrobně popisuje vývoj exportních úvěrových agentur se zvláštním zaměřením na služby, které tyto organizace poskytují malým vývozcům. Dewit (2001) Další části tohoto článku jsou organizovány následujícím způsobem. V části 1 je popsán mezinárodní rámec podpory exportu se zaměřením na existující dohody WTO a OECD.…”
Section: úVodunclassified
“…In addition, to develop EI, it needs to preserve standard rules and regulations, to provide insurance through website, exporters need to access to information export market insurance, etc. Dewit (2001) analyzed the behaviors of the operators against export risks, especially credit risk, and how they handle such risks. The study demonstrated that the export activity was strongly based on traditional markets, with little effort of detecting new market niches.…”
Section: Introductionmentioning
confidence: 99%